E2 Ubiquitin-Conjugating Enzymes Regulates Dengue Virus-2 Replication in Aedes albopictus - Jiaqi Wang; Xueli Zheng; Xuexue Wang; Daibin Zhong; Guofa Zhou (Microorganisms)
Aedes albopictus, a major vector of dengue virus (DENV), has a global distribution. Identifying the key components of the ubiquitin system of A. albopictus essential for the replication of viruses could help identify targets for developing broad-spectrum antiviral strategies. This study explores the interaction between E2 ubiquitin-conjugating enzymes (Ubc9) and DENV-2 proteins (NS1, NS5, and E) using cell culture and mosquito models. The replication of DENV-2 and the knockdown efficiency of the Ubc9 gene were assessed through reverse transcription–quantitative polymerase chain reaction. The DENV-2-related protein expression was evaluated via Western blot analysis. The interaction between Ubc9 and DENV E and NS5 proteins was investigated through confocal immunofluorescence and co-immunoprecipitation. RNA interference technology was employed to silence Ubc9 expression in C6/36 cells and in A. albopictus mosquitoes. The expression level of Ubc9 in the DENV-2-infected group was 3.5-fold higher than that in the control group. The Ubc9 gene expression in the midgut tissue of the mosquito was significantly upregulated. Transfection of C6/36 and BHK-21 cells with the pAc5.1b-EGFP-Ubc9-HA vector led to the overexpression of Ubc9, which decreased the transcription levels of DENV E and NS1, NS5 proteins. The difference was statistically significant (F = 24.27, p < 0.01). The expression levels of DENV NS5 and E proteins significantly decreased after infection with DENV-2, suggesting that the depletion of Ubc9 may limit the replication of DENV-2. Ubc9 regulates DENV-2 replication through SUMOylation in the cells and A. albopictus, potentially affecting vector competence and DENV transmission. This is the first study to demonstrate that the Ubc9 of A. albopictus plays a significant role in regulating the replication of DENV in both mosquito cells and the mosquito itself. The study results may prove useful in designing appropriate therapeutic approaches for dengue and associated complications.